Adaptation of basil to salt stress: Molecular mechanism and physiological regulation - Michele Ciriello; Giovanna Marta Fusco; Giuseppe Colla; Marios C. Kyriacou; Leo Sabatino; Stefania De Pascale; Youssef Rouphael; Petronia Carillo (Plant Stress, 2024)
Although many molecular and physiological mechanisms behind plant responses to osmotic and nutritional stresses (primarily salinity) have been identified, the strong impact of genetics makes understanding their interconnections complex. Moreover, the dominant genetic effect often masks other potentially influential factors modulating plant response to environmental stimuli. Using three types of basil (Dark Opal, Italiano Classico, and Purple Ruffles) that have different counteracting potentials to react to NaCl (60 mM) salt stress, we showed that higher constitutive concentrations of osmolytes and antioxidant molecules improve basil adaptation to a saline environment. An already active ROS scavenging mechanism and unaltered NUE allowed Purple Ruffles to remain unaffected by the toxic effects of salt, unlike Italiano Classico and Dark Opal, which incurred fresh yield reduction by 46.34 and 33.33 %, respectively. Up-regulation of secondary metabolism in response to biostimulant treatments (protein hydrolysate and protein hydrolysate+leaf liquid integrator) ensured a higher fresh yield in all basil types, regardless of salt treatment. Understanding the key molecular traits implicated in plant response to salinity is undoubtedly valuable for future genetic improvement programs of tolerant genotypes and for the application of products with biostimulatory and ameliorative action.